An Unusual Case of Mixed Respiratory Capillariosis in a Dog - Morelli, Simone (Pathogens, 2021)
Nematodes belonging to the genus Capillaria infect a range of domestic and wild animals. Capillaria aerophila and Capillaria boehmi cause respiratory parasitoses in dogs and wild carnivores, e.g., foxes and mustelids, although they are often overlooked in canine clinical practice. The present report describes an unusual case of a severe and mixed infection by C. aerophila and C. boehmi in a privately housed dog that showed acute and life-threatening respiratory and neurological signs. Clinic-pathologic and epizootiological implications are described and discussed.